First-in-human study to evaluate the safety, tolerability, and population pharmacokinetic/pharmacodynamic target attainment analysis of FL058 alone and in combination with meropenem in healthy subjects - Huang, Zhiwei; Yang, Xinyi; Jin, Yi; Yu, Jicheng; Cao, Guoying; Wang, Jingjing; Hu, Yingying; Dai, Jingyi; Wu, Jufang; Wei, Qiong; Tian, Yan; Yu, Shuyan; et al. (Antimicrobial agents and chemotherapy, 2024)
FL058 is a novel diazabicyclooctane β-lactamase inhibitor. This first-in-human study evaluated the safety, tolerability, and population pharmacokinetic (PK)/pharmacodynamic target attainment analysis of FL058 alone and in combination with meropenem in healthy subjects. The results showed that the maximum tolerated dose of FL058 was 3,000 mg after single-dose infusion. FL058 in combination with meropenem did not cause any grade 3 or higher adverse event when the dose was escalated up to 1,000 mg/2,000 mg. FL058 exposure PK parameters showed dose proportionality. FL058 was excreted primarily in urine. No significant PK interaction was found between FL058 and meropenem. Population PK model analysis indicated that the PK profiles of FL058 and meropenem were consistent with the two-compartment model. The impact of covariates, creatinine clearance, concomitant use of meropenem, body weight, sex, and FL058 dose, on FL058 exposure was less than 10%. FL058/meropenem combination was safe and well tolerated up to a 1,000-mg/2,000-mg dose in healthy adults. The recommended minimum dose of FL058/meropenem combination was 500 mg/1,000 mg by intravenous infusion over 2 h every 8 h based on target attainment analysis. The good safety, tolerability, and satisfactory PK profiles of FL058 alone and in combination with meropenem in this first-in-human study will support further clinical development of FL058 in combination with meropenem in patients with target infections (ClinicalTrials.gov identifiers: NCT05055687, NCT05058118, and NCT05058105).